The Impact of World Crude Oil Price Changes on the Malaysian Economy: an Input-Output Analysis - M. Yusof, Saari; Ahmad Fauzi, Puasa; Khairul Hisyam, Hassan (Malaysian Economic Association, 2007)
By using an input-output model, this paper attempts to examine the economic impact on the Malaysian economy resulting from an increase in crude oil petroleum price. By simulating different levels of crude oil prices, we found that an increase in the world crude oil petroleum price gives more capacity to the economy in generating output and revenue collected by the government in the form of direct and indirect taxes. However, it is very clear that if the crude oil price reaches USD60/barrel, the government will be required to subsidise about RM8.27 of the petrol retail price in order to maintain the current price level.